Internal Surface Roughness Profile Analysis of Brass Pipes - Raman Kumar, Sandeep Singh (International Journal of Advanced Science and Technology, 2020)
Surface  finish  has  a  crucial  role  in  the  friction  losses  in  pipes  of  various materials.  Higher surface finish enables the better fluid flow. In present work, the effect of numerous analytical factors such as sliding velocity, number of cycle and concentration ratio on surface roughness of Brass UNS C26800 is examined. Surface roughness (Ra) average values were calculated from mean of 8 values and percentage improvement in roughness is estimated. As readings were taken from the surface roughness tester (Mitutoyo Surftest SJ-210), the profiles were generated with the help of communication tool during internal surface testing of pipes taken for the experiment before and after experimentation. The experiments are selected randomly with comparatively different process parameters that offered best results out of the entire practice.